2021
DOI: 10.1186/s12893-021-01405-x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of management of intestinal obstruction at an urban tertiary hospital in sub Saharan Africa: a cross-sectional study

Abstract: Background Intestinal obstruction (IO) is a common cause of acute abdomen globally, it remains challenging as it increases surgical financial expenditure while also causing major morbidity. Clinically it presents with nausea, vomiting, colicky abdominal pain and cessation of bowel movements or passage flatus and stool. Diagnosis, especially in resource limited settings, can be clinical but is usually confirmed radiologically. We studied the current diagnosis, management and outcomes of IO in Mu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…1 , 2 , 6 Our study showed a male predominance (65%) in patients presenting with IO with a male to female ratio of 1.85:1 which is also comparable to the studies done in African countries: Nigeria (Male:Female= 2:1) and Uganda (Male:Female= 2.6:1); but lesser as compared to two independent studies done in South India (Male: Female= 4:1) and East India (Male:Female= 3:1). 12 , 7 , 8 The most common age group affected according to our study was 48-58 years, which is consistent with the studies done in East India (41-50 years) and South India (51-60 years). 1 , 2 …”
Section: Discussionsupporting
confidence: 92%
“…1 , 2 , 6 Our study showed a male predominance (65%) in patients presenting with IO with a male to female ratio of 1.85:1 which is also comparable to the studies done in African countries: Nigeria (Male:Female= 2:1) and Uganda (Male:Female= 2.6:1); but lesser as compared to two independent studies done in South India (Male: Female= 4:1) and East India (Male:Female= 3:1). 12 , 7 , 8 The most common age group affected according to our study was 48-58 years, which is consistent with the studies done in East India (41-50 years) and South India (51-60 years). 1 , 2 …”
Section: Discussionsupporting
confidence: 92%
“…This is similar to what is found in the literature. Nakanwagi et al 18 evaluated 135 patients who required emergency management for IO, showing that 72.7% of the patients required surgical management with bowel resection and anastomosis, a comparable result with our population 18 . Additionally, a study published by Mancini et al 19 which sought to compare the laparoscopic approach and open surgery for IO, found that 88.6% of patients required open approach and 11.4% required the laparoscopic approach with a conversion rate of 17.2%.…”
Section: Discussionsupporting
confidence: 80%
“…For patients with advanced gastric cancer, distant metastasis of cancer tissues and cells is easy to occur, resulting in a large range of lymph node dissection and large gastrointestinal stimulation during gastric cancer surgery. After surgery, due to the decrease of gastrointestinal motion amplitude and degree, an internal hernia or intestinal loop is generated between the intestines, which eventually leads to acute intestinal obstruction [ 13 ]. Clinical treatment of intestinal obstruction is mostly symptomatic treatment and surgical treatment, among which surgical treatment is more stimulating and damaging to the body and prone to postoperative adverse events [ 14 ].…”
Section: Discussionmentioning
confidence: 99%